Increased fetal lung T2 signal is not due to increasing surfactant concentration: an in vitro T2 mapping analysis. (25th January 2017) - Dubinsky, Theodore J.; Moshiri, Mariam; Waldorf, Kristina Adams; Wilson, Greg; Maki, Jeffrey H.; Hippe, Daniel S.
Abstract: Object: The aim of this study was to perform in vitro T2 mapping of serial dilutions of pharmaceutical surfactant. Materials and methods: Magnetic resonance imaging. Magnetic resonance scanning was performed on serial dilutions of surfactant on large bore clinical magnets at a field strength of 1.5 T Philips and 3.0 T (Achieva TX, Philips Healthcare, the Netherlands). Results: The curves demonstrate a small increasing trend between surfactant concentration and R2 (shortened T2's), with a 7.3% increase in R2 for each doubling of surfactant concentration (95% confidence interval: 6.1–8.6%, p  < 0.001). Conclusions: The increasing lung/liver T2 signal ratio seen in fetal lungs with increasing gestational age is not due to increasing surfactant concentration. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? T2 signal increases in fetal lungs with gestational age. What does this study add? Mechanism of why this occurs